Drone system for risk management - Cano López, Cristian Eduardo; Casas Méndez, Yeny Liliana; Santana Páez, Luisa Fernanda; Villamil León, William Steven (Ingeniería Solidaria, 2023)
This article is a product of the project "Estudio para identificar las capacidades tecnológicas en las pymes de la Villa de San Diego de Ubaté", developed by the Creing seedbed of the systems engineering program of the Universidad de Cundinamarca Seccional Ubaté during the year 2022.Objective: To develop an assistance system using unmanned aerial vehicles (drones) to support the Fire Department in risk management in the Villa de San Diego Ubaté.Method: Research conducted around the use of different programming languages for the creation of the website, trying to maintain the optimization of, where the user can find all the information about the service, likewise, is included mathematical and physical research with which you can analyze the flight characteristics according to the properties of the drone.Results: Mathematical and physical research applied to the analysis of the flight characteristics is evidenced, taking into account the properties and functionalities of the drone.[1]and the geographical details of the municipality of Ubaté-Cundinamarca, a bibliographic inquiry where the history, classification and Colombian regulations are supported, as well as the planning and the different tools and activities that are developed for the achievement of the project.Conclusion: The use of drones in different fields has intensified in recent years, however, although they are very useful for quick access to areas with difficulties or precarious situations, drone systems have not been implemented that allow surveillance and attention to these situations in a timely manner in the northern area of the department of Cundinamarca.Limitation of the study: this project is focused on the study and analysis for the municipality of Villa de San Diego de Ubaté due to the relevance of the sector and the study, as well as the ease of information gathering.
Keywords: research; Ubaté; natural disaster accidents; drones; geolocation